Richard Rorty’s comparatism (literature and philosophy) - Jiménez, Mauro (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In the field of philosophy the work of the American thinker Richard Rorty has deserved special attention for its controversial proposal to consider the philosophical discourse as new kind of literary discourse and, therefore, a new literary genre. However, to understand the thought of Richard Rorty in all its radicalism is necessary to perform a reading of his work based on comparative literature and not just philosophy. Note that in his later years Rorty developed his teaching at Stanford University as a professor of comparative literature. In this essay I try to explain his proposal from the field of comparative literature (and, consequently, from literary theory).